City-level estimation of vehicle CO2 emission factors regarding driving behaviors: The case of Tianjin, China - Haipeng Ye; Yu Li; Ji Zheng; Zehong Li (Heliyon)
The estimation of CO2 emission factors (EFs) is a key step in calculating automobile CO2 emissions. However, city-level research on the integrated estimation of vehicle CO2 EFs under real conditions is insufficient. To enrich the research methods of city-level vehicle CO2 EFs, this paper constructs a vehicle–road–driver three-layer regression model and estimates vehicle CO2 EFs empirical parameters for Tianjin. The results show that the influences of vehicle CO2 EFs can be ranked as follows: engine displacement level (0.740) > total mileage (0.336) > driving habit after the start (−0.072) > vehicle size (0.064). The average empirical parameter of Tianjin's vehicle CO2 EFs is 195.38 g/km. This study can provide a method to estimate vehicle CO2 EFs at city level, enrich the Chinese EFs database in the transport sector, and provide scientific support to formulate integrated low-carbon transport policies.